Dissolved Reactive Phosphorus Loads to Western Lake Erie: The Hidden Influence of Nanoparticles. Issue 3 (1st May 2019) - River, Mark; Richardson, Curtis J.
Abstract : Increased dissolved reactive phosphorus (DRP) fluxes in the Maumee River in the Western Lake Erie watershed have been cited as a cause of recent hypoxia and toxic algal blooms in Western Lake Erie. Dissolved reactive P is operationally defined as the molybdate‐reactive P that passes through a 0.45‐μm filter. Unfortunately, this 0.45‐μm cutoff is not based on solute chemistry; rather, it is based on tradition dating back to the 1940s. This dissolved versus particulate operationally defined threshold may be limiting scientific understanding of the transport of reactive P in the Lake Erie watershed (and beyond). Naturally occurring nanoparticles smaller than 0.45 μm can pass through filters, inflating DRP values, as has been suggested by studies in other watersheds. Transmission electron microscopy of filtered samples from the Maumee River revealed nanoparticles of various mineralogy, which are rich in P. By analyzing public data, we estimate that approximately half of the DRP flux in the Maumee River is not truly dissolved orthophosphate; it is instead particulate P that has passed through 0.45‐μm filters. We also conducted a centrifugation experiment on previously filtered samples that likewise removed 40% of DRP and 75% of Fe. The influence of nanoparticles on DRP loads to Lake Erie has implications, including (i) helping to elucidate where reactive P originates on the landscape, (ii) designing best management practices, and (iii) improving our models of ecological response of nonpoint P loading. Core Ideas: The role of nanoparticles in transporting P to Lake Erie is largely ignored. 0.45‐μm filtrate contained nanoparticles rich in P, inflating dissolved reactive P concentrations. Nanoparticles were responsible for approximately half of dissolved reactive P flux.